Serotyping of Streptococcus pneumoniae strains by coagglutination and counterimmunoelectrophoresis. - Trollfors, B (1983)
A total of 217 Streptococcus pneumoniae strains were serotyped by coagglutination (COA) and counterimmunoelectrophoresis (CIE). With all strains tested, there was full agreement between results obtained by COA and CIE, except for strains belonging to serotypes 7, 14, 33, and 37, which could not be typed by CIE. These strains were serotyped by passive immunodiffusion, results of which were in full agreement with those obtained by COA. Besides having the advantage of identifying strains belonging to all serotypes, COA was also more rapid and economical than CIE.